Listener satisfaction on Dayak song / John Rishi Onell - Onell, John Rishi (2007)
Entertainment is part and parcel of human life. Every human needs some kind of entertainment to balance his or her social life. Human needs to relax their mind from their daily activities. Music is one ofthe entertainments that human can hook to. In fact, as we listen to music we do not purposely choose to listen to it but simply come so naturally into our mind. Later, that natural interest generates our action to find the type of music that we want. Music itself is an art. It needs skills to compose and develop them. Music is also a way of people can express their feelings. To some people music is the best or one ofthe ways they can express their feelings and thoughts. “Human beings are (almost) the only mammal species that possesses both speech and music. Almost means here: Whales and dolphins communicate by sounds, wolves howl and singing birds know melodies. What speech is good for is very clear: we use it to communicate our thoughts to our fellow humans. But why do humans need music? Every single human being, male or female, handicapped or not, young or old, has s desire to sing and dance and to listen to music, just like everybody has a desire for food and drink, for sex and sleep.